19 The randomised complete vs. lesion only primary PCI trial – cardiovascular MRI substudy (CVLPRIT-CMR). (26th April 2015) - Khan, JN; Greenwood, JP; Nazir, SA; Dalby, M; Curzen, N; Hetherington, S; Kelly, DJ; Blackman, D; Ring, A; Peebles, C; Wong, J; Flather, M; et al.
Abstract : Background: Multivessel disease (MVD) occurs in ~40% of STEMI. Management is controversial. PRAMI and CVLPRIT showed improved clinical outcomes with complete versus infarct-related artery (IRA)-only revascularisation at primary percutaneous coronary intervention (PPCI). However, non-IRA PCI may cause additional infarcts. We aimed to determine whether in-hospital complete revascularisation was associated with increased myocardial injury versus an IRA-only strategy. Methods: Multicentre, prospective, randomised, blinded endpoint trial. STEMI patients with MVD and <12 hr symptoms were randomised to IRA-only or complete in-hospital PCI. 1.5T CMR was performed acutely (median 3 days post-PPCI) and with adenosine stress at 9 months. The primary CMR endpoint was acute infarct size on late gadolinium imaging. Myocardial salvage index (MSI) was the proportion of non-infarcted area-at-risk. n = 100 per group gave 80% power to detect ±4% infarct size. The primary clinical outcome was 12 month combined MACE (death, repeat revascularisation, heart failure, MI). Validation studies optimised infarct, area-at-risk and strain quantification. Full-width half-maximum infarct quantification was more accurate, reproducible and correlated strongest with ejection fraction (LVEF) and infarct characteristics. Otsu's Automated Thresholding most accurately and reproducibly assessed area-at-risk. Compared with tagging, Feature Tracking strain measurement was more robust, quicker, had better interobserver variability and correlated stronger with infarct, area-at-risk and MSI. Results (summarised in Table 1): 203 patients (98 complete revascularisation, 105 IRA-only) completed acute CMR. The groups were well matched. There was no difference in infarct size, MSI, LVEF, circumferential strain or ischaemic burden between groups. Complete revascularisation patients had increased non-IRA MI at acute CMR (Figure 1 ). 12 month MACE was reduced in complete revascularisation patients (8.2% vs. 17.1%, p = 0.055, hazard ratio 0.43). Conclusions: Complete revascularisation in STEMI with MVD leads to a small increase in CMR-detected non-IRA MI, but total infarct size and 12 month MACE are not increased. This provides further reassurance that complete revascularisation can be considered at PPCI.